THE CHANGES OF MANDIBULAR ROTATION AND LOWER ANTERIOR FACIAL HEIGHT IN DENTOSKELETAL ORTHODONTIC TREATMENT WITH MALOCCLUSION CLASS II/1 ANGLE - Wahyuni Dyah Parmasari; Enny Willianty; Theodora Theodora (FKG Unlam, 2022)
Background: Classification of malocclusion, especially in the class II division, has various biological variations and dental abnormalities with the presence of distocclusion of the first molar relation and proclination of the maxillary fourth incisor and causing the patient's profile to become convex. Aesthetic correction in class II division 1 is determined by the choice of treatment and taking into account the rotational pattern of the mandible. Objectives: To determine the effect of orthodontic treatment in relation to changes in mandibular rotation with lower anterior facial height and to determine the parameters of the effect of mandibular rotation on lower anterior facial height (LAFH) in Angle Class II/1 dentoskeletal malocclusion. Methods: Cephalometric data were obtained from lateral cephalograms presented before and after treatment. Assessed changes in Y-axis FH angle, SN - mandibular plane angle (GoMe) and NPog-FH angle facial angle. Data analysis with Pearson was used to correlate the mandibular rotation parameter (angle) with the lower anterior facial height parameter, namely ANS-Me (linear) (p > 0.05). Results: Group 1 access maxilla, normal mandible showed a significant correlation on the Y-FH Axis with ANS-Me. Group 2 with normal maxillary, retrognathic mandibles, showed a significant correlation between NPog-FH with ANS-Me and NPog-FH with extrusion of the upper/lower first molars. Group 3, the combination group which is the maxillary retrognathic access, showed a significant correlation between Sn-GoMe and ANS-Me. Group 4 is with different teeth, but normal bone (grade 1). Conclusion: There is a relationship between changes in mandibular rotation and changes in lower anterior facial height (LAFH) in the orthodontic treatment of class II/1 Angle dentoskeletal malocclusion.